Some Experiments in Demand Analysis - Prest, A. R. (The Review of Economics and Statistics, 1949)
THE main purpose of this article is to record and analyze the results of some investigations into United Kingdom consumption data over the period I870-I938. The discussion is arranged in three sections consisting respectively of a brief survey of the economic and statistical problems involved, a summary of the data used and the results obtained, and an appraisal of the significance and value of these results. It should be emphasized at the outset that section I is little more than a survey of the work done in this field by others.' The main contribution which it is hoped will be made by this article is to extend these ideas and formulations over a longer time-period than has previously been attempted with United Kingdom data.